Brain co‐delivery of first‐line chemotherapy drug and epigenetic bromodomain inhibitor for multidimensional enhanced synergistic glioblastoma therapy. Issue 4 (19th April 2022) - Liu, Yanjie; Wang, Wendie; Zhang, Dongya; Sun, Yajing; Li, Fangzhou; Zheng, Meng; Lovejoy, David B.; Zou, Yan; Shi, Bingyang
Abstract: Glioblastoma (GBM) is a central nervous system tumor with poor prognosis due to the rapid development of resistance to mono chemotherapy and poor brain targeted delivery. Chemoimmunotherapy (CIT) combines chemotherapy drugs with activators of innate immunity that hold great promise for GBM synergistic therapy. Herein, we chose temozolomide, TMZ, and the epigenetic bromodomain inhibitor, OTX015, and further co‐encapsulated them within our well‐established erythrocyte membrane camouflaged nanoparticle to yield ApoE peptide decorated biomimetic nanomedicine (ABNM@TMZ/OTX). Our nanoplatform successfully addressed the limitations in brain‐targeted drug co‐delivery, and simultaneously achieved multidimensional enhanced GBM synergistic CIT. In mice bearing orthotopic GL261 GBM, treatment with ABNM@TMZ/OTX resulted in marked tumor inhibition and greatly extended survival time with little side effects. The pronounced GBM treatment efficacy can be ascribed to three key factors: (i) improved nanoparticle‐mediated GBM targeting delivery of therapeutic agents by greatly enhanced blood circulation time and blood–brain barrier penetration; (ii) inhibited cellular DNA repair and enhanced TMZ sensitivity to tumor cells; (iii) enhanced anti‐tumor immune responses by inducing immunogenic cell death and inhibiting PD‐1/PD‐L1 conjugation leading to enhanced expression of CD4 + and CD8 + T cells. The study validated a biomimetic nanomedicine to yield a potential new treatment for GBM. Abstract : We developed temozolomide and epigenetic bromodomain inhibitor co‐encapsulated biomimetic nanomedicine (ABNM@TMZ/OTX) achieved multidimensional enhanced glioblastoma synergistic chemoimmunotherapy in both primary and recurrent orthotopic mice models with significant extended survival rate and little side effects.